Anisotropic compressional behaviour of the Sorel cement F5-phase (Mg3(OH)5Cl·4H2O). (22nd February 2023) - Battiston, Tommaso; Comboni, Davide; Verri, Giancarlo; Hanfland, Michael; Gatta, G. Diego
Graphical abstract: Highlights: High-pressure study of the F5-phase, the main binder component of the Sorel cement. Description of the elastic parameters in two different compressional regimes. Re-investigation of the F5-phase crystal structure by synchrotron X-ray diffraction. Deep characterization of the H-bonding network governing the structure stability. Abstract: The crystal structure of the so-called F5-phase [Mg3 (OH)5 Cl·4H2 O], the dominant crystalline component of the Sorel cement, has been reinvestigated by synchrotron powder X-ray diffraction data, with a deep description of the complex and pervasive H-bonding network. Its isothermal high-pressure behaviour (up to 5.10 GPa) has been studied by an in-situ compressional experiment, under hydrostatic conditions. The pressure vs volume pattern, modelled with an isothermal equation of state, revealed the occurrence of two anisotropic compressional regimes: the values of the isothermal bulk modulus ( K 0  =  −  V (∂ P /∂ V )) is 28.2(5) and 38.5(9) respectively up to 1.90 and at P  > 2.10 GPa. The F5-phase shows a significant anisotropic compressional scheme, described as magnitude and orientation of the Eulerian finite unit-strain ellipsoid: ε1:ε2:ε3 ∼ 6.6:2.5:1.0 up to 1.9 GPa, and ε1:ε2:ε3 ∼ 4.7:1.8:1.0 at P  > 2.1 GPa for the low- and high- P regimes, respectively. The structural causes, at the atomic scale, that govern the compressional anisotropy of the F5-phase are discussed.